Determining the factors associated with women's participation in household decision-making - Reyes, Samantha Rae M.; Sabarre, Javier Gaspar M.
This study explores the determinants of Filipino women’s participation in household decision-making in relation to Resource Theory, Gender Theory and household characteristics. The objective of the paper is to determine whether the factors, which determine women’s participation in household decision- making are consistent with previous theoretical and empirical literature, as well as to add onto pre-existing studies. Using pooled data from the 2003, 2008, 2013, and 2017 Philippines National Demographic and Health Survey (NDHS) conducted by the Philippine Statistical Authority (PSA), four logistics regressions were used pertaining to a woman being able to decide in: 1) her own health decisions, 2) major household decisions, 3) family or relative visits, and 4) at least one of the three aforementioned categories. Our findings show that in relation to Gender Theory, the woman’s age and having a female household head prove to be robustly positively correlated with a woman’s participation in household decisions. However, the estimation results with regard to Resource Theory and household characteristics show mixed results.